2021
DOI: 10.1080/13613324.2021.1924137
|View full text |Cite
|
Sign up to set email alerts
|

Racism camouflaged as impostorism and the impact on Black STEM doctoral students

Abstract: Black doctoral students in engineering and computing fields experience racialized stress, as structural racism in STEM takes a toll on their sense of belonging and acceptance as intellectually competent in comparison to White and some Asian peers and faculty. Black doctoral students are often told by campus administrators that the source of this racialized stress is impostorism and it is curable. In this article, we employ phenomenological analysis to examine how 54 Black engineering and computing students exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 56 publications
(70 reference statements)
3
56
0
1
Order By: Relevance
“…Their own racial and ethnic marginalization, and the ways they have suffered personally and professionally, translate into concern about local and global disparities. This equity ethic has been a key motivation for their persistence in STEM, and their desire to catalyze change, improve communities, and be the supportive Black STEM professor many of their students never had (McGee, 2020a; McGee et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Their own racial and ethnic marginalization, and the ways they have suffered personally and professionally, translate into concern about local and global disparities. This equity ethic has been a key motivation for their persistence in STEM, and their desire to catalyze change, improve communities, and be the supportive Black STEM professor many of their students never had (McGee, 2020a; McGee et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The four prior studies cited primarily focused on race-based experiences of impostor phenomenon (Burt et al, 2017;McGee et al, 2019McGee et al, , 2021 as well as documented, through a survey at one US institution, that women in computer science experienced impostor phenomenon more than men (Rosenstein et al, 2020). Although these studies examined why engineers experienced impostor phenomenon, focusing on its implication in STEM fields, the reasons engineering education researchers experience this phenomenon have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In the third study, more than 200 undergraduate and graduate students in computer science were surveyed using the Clance Impostor Phenomenon Scale (CIPS) (Clance, 1985) at one large, research university in the US (Rosenstein et al, 2020), revealing that a majority of students (especially women) in computer science experienced impostor phenomenon frequently. In the fourth and more recent (interview) study, 54 doctoral students in engineering and computing who identify as Black revealed that they experienced systemic racism that was positioned as impostor phenomenon (an irrational individual behavior) by campus administrators (McGee et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Minoritized students often encounter STEM PhD environments which are hostile and unsupportive due to competitive, meritocratic and supposedly colorblind cultures which conceal the reality of institutional racism that exists in these spaces (Basile and Lopez, 2015; Bonilla-Silva, 1997; Brunsma et al , 2017). Broadly, this institutional culture ignores the racial identities of scientists through a framework which centers on individuated aptitude (Armstrong and Thompson, 2003; McGee et al , 2021; Seymour et al , 1997). For example, a student participant within a 2017 study conducted by McGee and Bentley (2017) reported that her advisor advised her to not worry about her skin color and just focus on her academic work.…”
Section: Introductionmentioning
confidence: 99%